State fragility, rent seeking and lobbying: evidence from African data - Simplice A. Asongu; Oasis Kodila-Tedika (African Governance and Development Institute (AGDI), 2013)
This paper assesses the determinants of state fragility in sub-Saharan Africa using hitherto unexplored variables in the literature. The previously missing dimension of nation building is integrated and the hypothesis of state fragility being a function of rent seeking and/or lobbying by de facto power holders is tested. The resulting interesting finding is that, political interference, rent seeking and lobbying increase the probability of state fragility by mitigating the effectiveness of governance capacity. This relationship (after controlling for a range of economic, institutional and demographic factors) is consistent with a plethora of models and specifications. The validity of the hypothesis is confirmed in a scenario of extreme state fragility. Moreover, the interaction between political interferences and revolutions mitigate the probability of state fragility while the interaction between natural resources and political interferences breeds the probability of extreme state fragility. As a policy implication, there is a 'sub-Saharan African specificity' in 'nation building' and prevention of conflicts. Blanket fragility oriented policies will be misplaced unless they are contingent on the degree of fragility, since 'fragile' and 'extreme fragile' countries respond differently to economic, institutional and demographic characteristics of state fragility.
Keywords: C43; H11; O20; O43; O55; 330; State fragility; rent seeking; lobbying; nation building; Africa